Chemical characterization of humic substances occurring in the peats of Sarawak, Malaysia - Sim, Siong Fong; Murtedza, Mohamed (Elsevier Ltd., 2007)
The chemical characteristics of humic substances (HS) extracted from several samples of peat soils of Sarawak, Malaysia, were determined by size exclusion chromatography, FTIR, UV–Vis, acid–base titration, and elemental and total hydrolysable carbohydrate analyses. The results showed that the total acidity of these HS ranged between 5.8 and 8.3 meq/g, with a clear indication that the fulvic acid component contained more carboxylic groups compared to humic acids. A comparison with the literature data for HS occurring elsewhere showed that the tropical peat of Sarawak has higher carboxylic and phenolic contents, is richer in carbohydrate moiety and also is more oxygenated. The UV–Vis analyses gave a relatively high E4/E6 ratio, implying the prominence of aliphatic components. The relatively lower range of Mw further suggested the dominance of smaller-sized humic molecules. These structural attributes suggest that the local HS may exhibit a strong complexing capability and greater susceptibility to electrophilic cleavage by trihalomethane-forming agents.